PERANCANGAN VIDEO PROFILE SEBAGAI MEDIA PROMOSI DAN INFORMASI DI SMK AVICENA RAJEG TANGERANG - Wahyu Hidayat; Anita B. Wandanaya; Recha Fadriansyah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Technological development especially in the field of information and communications has grown in such a rapidly especially in the field of multimedia. This is according to an institution to develop information from various media in accordance with the development. A wide variety of media promotion and the information is urgently needed, for it required media interactive and efficient promotion in order to attract students and new students. one of the interactive and efficient media are audio visual media. SMK Avicena Rajeg Tangerang is the agency or educational institution that is always in order to improve the quality of education bersain in the current era of globalization, but the school has not had media full and effective information about the school profile at once can be a means of promotion to the public. Then a study with the title "Designing Video Profile as a Media promotion and information in SMK Avicena Rajeg Tangerang". As media promotion as well as information that can be seen by the wider community. By using audio visual methods are expected to provide promotional and information effectively and efficiently, so that the end results were achieved from the writing of this report, namely the creation of a draft media promotion and information video-shaped profile that is effective and according to your needs and are able to improve target marketing.